Recommendations and a guideline for referral of infantile haemangioma to tertiary centres - Strumila, Arūnas; Dagilytė, Rūta Vilija; Beiša, Virgilijus (Acta medica Lituanica, 2018)
Background. Infantile haemangioma is the most common childhood vascular tumour, which causes great anxiety to parents and treating firstline physicians due to its proliferative nature. It accounts for a large percentage of a tertiary centre consultations, thus delaying consultation time for patients in need of immediate care. Materials and methods. Review of literature and experience of treatment and observation of infantile haemangiomas in a tertiary centre of paediatric surgery. Results. Based on the gathered information, we established an observation guideline of infantile haemangiomas for first-line physicians. Conclusions. First-line physicians must recognise the infantile haemangioma that requires immediate referral to a tertiary centre in order to prevent the appearance of associated complications. The remaining population of the patients of infantile haemangioma can be actively monitored once a month for at least a year by the treating pediatrician or family doctor. New and easy to use protocoled diagnostic tests such as thermography would greatly benefit first-line and tertiary-centre physicians in the follow-up of infantile haemangiomas.